Small molecule targeting NaV1.7 via inhibition of the CRMP2-Ubc9 interaction reduces pain in chronic constriction injury (CCI) rats. Issue 1 (31st December 2022) - Li, Jiahe; Stratton, Harrison J.; Lorca, Sabina A.; Grace, Peter M.; Khanna, Rajesh
ABSTRACT: The voltage-gated sodium channel isoform NaV1.7 is a critical player in the transmission of nociceptive information. This channel has been heavily implicated in human genetic pain disorders and is a validated pain target. However, targeting this channel directly has failed, and an indirect approach – disruption of interactions with accessory protein partners – has emerged as a viable alternative strategy. We recently reported that a small-molecule inhibitor of CRMP2 SUMOylation, compound 194, selectively reduces NaV1.7 currents in DRG neurons across species from mouse to human. This compound also reversed mechanical allodynia in a spared nerve injury and chemotherapy-induced model of neuropathic pain. Here, we show that oral administration of 194 reverses mechanical allodynia in a chronic constriction injury (CCI) model of neuropathic pain. Furthermore, we show that orally administered 194 reverses the increased latency to cross an aversive barrier in a mechanical conflict-avoidance task following CCI. These two findings, in the context of our previous report, support the conclusion that 194 is a robust inhibitor of NaV1.7 function with the ultimate effect of profoundly ameliorating mechanical allodynia associated with nerve injury. The fact that this was observed using both traditional, evoked measures of pain behavior as well as the more recently developed operator-independent mechanical conflict-avoidance assay increases confidence in the efficacy of 194 -induced anti-nociception.